LINGUISTIC FEATURES OF SYMBOLS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS - Khakimova Surayyo Iskandarovna (Web of Journals Publishing, 2024)
This paper examines the linguistic features of symbols in the Uzbek and English languages, exploring how symbols function in both linguistic systems. Using a comparative analysis, we investigate how culturally significant symbols are encoded linguistically, focusing on both the lexicographical representation and socio-pragmatic aspects. Findings show that while both languages use symbols to convey cultural values and meanings, the manner in which these symbols are constructed and interpreted varies significantly based on historical, cultural, and socio-linguistic factors.
Keywords: Symbols, language, culture, comparative analysis, contextual meaning.